Pendampingan Pembelajaran Al-Qur’an dan Risalah Haid Melalui Pendekatan Andragogi pada TPQ Lansia di Dusun Kesamben Desa Bawangan Ploso Jombang - Unsi, Baiq Tuhfatul; Intan Nadiroh; Husnul Khotimah (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
This community service aims to improve the religious insight and reading skills of the people of Kesamben Hamlet, Bawangan Village, Ploso District, Jombang Regency, with a focus on the needs of the elderly in learning the Qur'an. The Participatory Action Research (PAR) method is used to ensure the active involvement of the community in the service process. Through participatory observation and interviews with community leaders, it was found that many elderly people were not able to read the Qur'an well, and previous learning programs were halted since the COVID-19 pandemic. In response, the researcher initiated the elderly TPQ program which was carried out three times a week, including the learning of the Qur'an and the Haidl Treatise. The results of the Religious Tradition Assistance program through the Andragogy Approach to TPQ for the Elderly in Kesamben Hamlet, Bawangan Village, Ploso, Jombang received a positive response from the community, with the active participation of twenty-five elderly people. Despite challenges such as time constraints and declining physical abilities of the elderly, a fun approach that uses an andragogy approach has succeeded in improving their ability to read the Qur'an and understand their religion. Keywords: Assistance, Religious Tradition, Andragogi, TPQ for the Elderly.